Multiple and multidrug resistance in Botrytis cinerea: molecular mechanisms of MLR/MDR strains in Greece and effects of co-existence of different resistance mechanisms on fungicide sensitivity - Sofianos, Georgios; Samaras, Anastasios; Karaoglanidis, Georgios (Frontiers in Plant Science, 2023)
Botrytis cinerea is a high-risk pathogen for fungicide resistance development. Within the fungal populations, strains have built up that possess multiple mutations in different target genes leading to Multiple Resistance (MLR) or mutations associated with overexpression of efflux transporters leading to Multidrug Resistance (MDR). These types of resistance are a major threat and their successful management is a major challenge. The current study was initiated to: a) determine frequencies of MLR/MDR strains in populations originating from several crops, b) identify the type(s) of MDR that occur in Greece and c) determine interactions between MLR and MDR in the level of sensitivity to botryticides. The frequencies of MLR/MDR phenotypes, were determined in 515 isolates subjected to bioassays using discriminatory concentrations of thiophanate-methyl, iprodione, cyprodinil, fenhexamid, boscalid, fluopyram, fludioxonil, pyraclostrobin and tolnaftate. Interestingly 7.8 and 31.3% of isolates from strawberry and rootstock seedlings were resistant to every single fungicide class, while MDR phenotypes from strawberry, rootstocks and tomato accounted for 26, 87 and 13.4% respectively. The MLR and MDR isolates were further molecularly analysed regarding genes erg27, sdhB, Bcpos5 and Mrr1, responsible for resistance to fenhexamid, boscalid and fluopyram, cyprodinil and MDR, respectively. The different mutations’ presence was determined along with a new mutation in Mrr1 leading to MDR. MDR isolates were characterised as MDR1 or MDR1h based on the presence of a 3-bp deletion in Mrr1. MDR1h was predominant in isolates from rootstocks and MDR1 from tomato and strawberry, whereas the most frequent target site mutations were F412S (erg27), H272R (sdhB) and L412F (Bcpos5). To determine whether the accumulation of target-site mutations along with MDR mutations exhibits an additive effect concerning fungicide resistance, the sensitivity of isolates possessing the predominant target site mutations was calculated both in the presence and the absence of MDR-associated mutations. EC50 in cyprodinil and boscalid increased to about 2-fold in the presence of MDR mutations, while there was no difference for fenhexamid. In conclusion, MLR/MDR frequencies are notably high in heavily-treated crops in Greece and the combination of MLR and MDR mutations leads to even higher fungicide resistance levels, highlighting the importance of resistance management.